TRANSFORMASI RELASI KELUARGA DI ERA DIGITAL: DAMPAK KETERGATUNGAN JUDI SLOT ONLINE PADA REMAJA - Juliyana Fitri; Huldiya Syamsiar; Hanapi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The widespread phenomenon of online slot gambling in today's digital era has triggered various social crises, one of which is the deterioration of family relationships. This study aims to analyze how online slot gambling transforms family relationships. The research employed a qualitative method with an Interpretative Phenomenological Analysis (IPA) design to explore and understand the lived experiences of the participants. The study involved nine participants, consisting of adolescents and parents. The findings reveal significant changes in family relationships. Family communication declined, conflicts increased, and trust among family members weakened. Adolescents addicted to online slot gambling tended to become less open and more socially withdrawn. Meanwhile, parents experienced difficulties in monitoring their children and maintaining effective communication. The study concludes that online slot gambling has a substantial negative impact on family interactions and the overall quality of family relationships in the digital era.